The Evolution of Manpower Management : A Historial Overview - Lundberg, C.; Mikalachki, A. (Relations industrielles / Industrial Relations, 1965)
The purpose of this paper is to show the evolution of manpower management by taking into accounts the socio-cultural context from which the need of conscious and rational personnel administration has originated.